Comparative analysis of selected programming frameworks of Java-based web applications - Książek, Radosław; Pańczyk, Beata (Journal of Computer Sciences Institute, 2022)
This article presents the results of a comparative analysis of Spring (with Spring Boot configuration), Micronaut and Quarkus programming frameworks. The recently observed increase in popularity of these solutions made it necessary to determine their application profile. In order to determine the characteristics of the researched technologies, a series of performance and optimization tests of applications built on the basis of the above-mentioned programming frameworks were carried out. The results of the analyzes showed that thanks to the high degree of optimization, the Micronaut and Quarkus skeletons are perfectly adapted to work in cloud environments, while Spring (Boot) framework, despite its lower efficiency, is an irreplacible solution in complex projects.